Three new species of oribatid mites of the family Galumnidae (Acari, Oribatida) from South Africa - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A.; Khaustov, Alexander A. (Zootaxa, 2021)
Three new species of oribatid mites of the family Galumnidae are described from soil and coniferous litter of Hogsback State Forest, Eastern Cape Province, South Africa. Pilogalumna hogsbackensis sp. nov. differs from Pilogalumna tenuiclava and P. ornatula by the presence of elongate oval postanal porose area and narrowly unilaterally dilated bothridial head. Pergalumna amatholensis sp. nov. differs from Pergalumna distincta by the presence of smaller body size, rounded rostrum, unilaterally dilated bothridial head, one pair of notogastral porose areas Aa, and the localization of opisthonotal gland opening and lyrifissure im. Stictozetes ihaguensis sp. nov. differs from all species of the genus by presence of bothridial seta with narrowly dilated head and median pore in both genders. An identification key to known species of Stictozetes is presented.